KENABIAN DAN PEWAHYUAN DALAM ISLAM - Andi Nurul Hidayat; Basmar; M. AMIN (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Prophethood and revelation are central concepts in Islamic theology that form the foundation for the legitimacy of Islamic teachings and laws. Through prophethood, Allah SWT conveys His divine guidance to humanity by means of revelation. This article aims to provide a comprehensive understanding of prophethood and revelation from an Islamic perspective, as well as to explain their relevance to Muslim life in the modern era. This study employs library research with a descriptive-analytical approach. The findings indicate that prophethood is a form of divine selection intended to guide humanity toward monotheism (tawhid) and moral conduct, while revelation functions as an authoritative medium for transmitting divine teachings that are preserved in their authenticity.